2019
DOI: 10.4110/in.2019.19.e3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Autoimmune Changes in Lacrimal Glands

Abstract: Aging is a complex process associated with dysregulation of the immune system and low levels of inflammation, often associated with the onset of many pathologies. The lacrimal gland (LG) plays a vital role in the maintenance of ocular physiology and changes related to aging directly affect eye diseases. The dysregulation of the immune system in aging leads to quantitative and qualitative changes in antibodies and cytokines. While there is a gradual decline of the immune system, there is an increase in autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 90 publications
2
23
0
1
Order By: Relevance
“…The changes in effector T cells were accompanied by increased populations of activated antigen-presenting cells in the DLNs, suggesting that an increased presence of the antigen is crucial to age-related dry eye, as previously reported [4]. High levels of IFN-γ in the conjunctiva are known to impact the loss of goblet cells [5,12]. Our study showed a decreased goblet cell density in 1Y-old mice, along with an increase in CD4 + IFNγ + cells in LG.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…The changes in effector T cells were accompanied by increased populations of activated antigen-presenting cells in the DLNs, suggesting that an increased presence of the antigen is crucial to age-related dry eye, as previously reported [4]. High levels of IFN-γ in the conjunctiva are known to impact the loss of goblet cells [5,12]. Our study showed a decreased goblet cell density in 1Y-old mice, along with an increase in CD4 + IFNγ + cells in LG.…”
Section: Discussionsupporting
confidence: 70%
“…Chronological changes in the LGs were reported in mice with mast cell infiltration, decreased peroxidase secretion, and lipofuscin accumulation at 8 to 12 months of age, followed by T and B lymphocytic infiltration, decreased innervation, decreased acetylcholine release, and structural changes up to 24 months of age [5,11,12]. Given the post-mortem changes in the LGs in humans, C57BL/6 mice can be used as a model to evaluate age-related DED, since C57BL/6 mice develop age-related dacryoadenitis, MG dysfunction, and corneal staining [5]. Interestingly, an aging-related predominance of IFN-γ-secreting CD4 + IFNγ + or CD4 + IL17 + cells in the LGs may depend on the sex of the rodent [5,12].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations